2007
DOI: 10.1016/j.neuint.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin and age on gene expression in mouse CNS using microarray analysis

Abstract: The expression levels of a number of genes associated with inflammation and immune function change with advancing age. Melatonin modulates gene expression levels of several of these genes. Therefore the declining levels of melatonin associated with age may play a role in the physiological effects of aging. We used oligonucleotide microarrays to measure age-related changes in mRNA expression in the murine CNS, and to study the effect of prolonged administration of dietary melatonin upon these changes. CB6F1 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…Results of an in vitro study revealed an increase in hsp60 gene expression after the cells were treated with MLT (Bonior et al, 2005). In contrast, the results of Sharman et al (Sharman et al, 2007) showed that MLT decreased hsp70 mRNA expression in brain tissues from aged mice.…”
Section: Introductionmentioning
confidence: 78%
“…Results of an in vitro study revealed an increase in hsp60 gene expression after the cells were treated with MLT (Bonior et al, 2005). In contrast, the results of Sharman et al (Sharman et al, 2007) showed that MLT decreased hsp70 mRNA expression in brain tissues from aged mice.…”
Section: Introductionmentioning
confidence: 78%
“…Martinez et al [28] reported that melatonin reduces the neuronal damage mediated by ROS. Melatonin has a powerful scavenging activity for hydroxyl and peroxyl radicals over that of both glutathione and vitamin E. Melatonin also conserves the activities of the antioxidant enzymes via enhancing gene expression of these enzymes [29]. Melatonin has a phenol group that provides a proton to detoxify hydroxyl or lipid peroxy radicals and thus can reduce lipid peroxidation induced by Al in Alzheimer's patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of immune response genes was previously demonstrated in murine and human brains (Lee et al 2000;Terao et al 2002). Specifically, the expression of the complement component genes C1qa, C1qb, C1qc, and C4b was increased in aged murine's hippocampus, neocortex, cerebellum, and whole brain (Blalock et al 2003;Burger et al 2008;Prolla 2002;Rowe et al 2007;Sharman et al 2007), and C1qa and C1qb expression levels were also upregulated in normal-aged human brains (Berchtold et al 2008). Interestingly, glial cells of AD patients secreted more C1q than nondemented elderly controls (Lue et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…We generated two lists of genes that were previously detected as changed in aging brains in eight mouse or rat expression microarray experiments (Blalock et al 2003;Burger et al 2008;Cho et al 2002;Jiang et al 2001;Kadish et al 2009;Prolla 2002;Rowe et al 2007;Sharman et al 2007) and in four human experiments (Berchtold et al 2008;Erraji-Benchekroun et al 2005;Lu et al 2004;Tang et al 2009). These studies profiled different gender compositions and samples from various ages.…”
Section: Previously Described Genes With Significant Expression Changmentioning
confidence: 99%
See 1 more Smart Citation